Assessment of the impact of dividend payout ratio on firm performance: A case of listed firms in Dar-es-salaam stock exchange - Ushahidi, Khadija (Mzumbe University, 2024)
A dissertation Submitted to Mzumbe University as a partial fulfillment of the requirements for award of the Degree of Master of Science in Accounting and Finance (MSc. A&F) of Mzumbe University